2015
DOI: 10.1680/macr.14.00179
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sieved coal bottom ash as a sand replacement on the properties of cement concrete

Abstract: This paper presents the results of an experimental investigation into the effects of sieved coal bottom ash (SCBA) as a replacement for natural sand on the properties of concrete. The compressive strength, split tensile strength, flexural strength and water permeability were studied. Natural sand was replaced with SCBA (0, 10, 20, 30, 40, 50, 60, 70, 80, 90 and 100% by weight) at a fixed water/cement ratio. The results indicate that there was a decrease in the density and workability of SCBA concrete with an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…M.P. Kadam et al [7] detected from his investigation that the density of concrete in hardened state was decreased linearly with increase in ratio of bottom. Tests unveiled that the density of 10 % replacement was increased by 0.04 % for 7 days, and then it was progressively decreased from 2.31% to 13.53%, 1.32% to 16.32%, 2.67% to 14.89% and 1.46% to 18.37% for cube specimen when fine aggregate was replaced from 10 % to 100 % by bottom ash at 7, 28, 56, and 112 days.…”
Section: B Bottom Ashmentioning
confidence: 96%
See 2 more Smart Citations
“…M.P. Kadam et al [7] detected from his investigation that the density of concrete in hardened state was decreased linearly with increase in ratio of bottom. Tests unveiled that the density of 10 % replacement was increased by 0.04 % for 7 days, and then it was progressively decreased from 2.31% to 13.53%, 1.32% to 16.32%, 2.67% to 14.89% and 1.46% to 18.37% for cube specimen when fine aggregate was replaced from 10 % to 100 % by bottom ash at 7, 28, 56, and 112 days.…”
Section: B Bottom Ashmentioning
confidence: 96%
“…M.P. Kadam et al [7] carried out Compressive strength tests of concrete mix made with and without coal bottom ash of cubes size 1.5 cm × 1.5 cm × 1.5 cm and the results were determined at 7, 28, 56, and 112 days. It was observed that for 10 % and 20 % sand replacement the compressive strength was increased by 4.6 %, 3.99 %, 0.61%, 0.20 % for 7, 28, 56 and 112 days respectively as compared with controlled concrete.…”
Section: Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Result of research about the using of coal ash waste (fly ash and/or bottom ash) as mixing in the concrete is among athers : Effect of coal bottom ash on the properties of concrete such as workability, bleeding, setting times, compressive strength, split tensile strength, flexural strength, shrinkage, and durability [6], Upgraded incinerator bottom ash can replace up to 20 % sand and/or gravel in reinforced concrete and up to 50 % in plain concrete [7], It was observed that up to 30% replacement the results of compressive, flexural, split and water permeability test are approximately same as that of the controlled concrete [8], The strength development for various percentages (0-50%) replacement of fine aggregates with bottom ash can easily be equated to the strength development of normal concrete at various ages [9], indicate significant improvement in the strength properties of plain concrete by the inclusion of fly ash as partial replacement of fine aggregate (sand), and can be effectively used in structural concrete [10].…”
Section: Introductionmentioning
confidence: 95%
“…M.P. Kadam et al [4] carried out Compressive strength tests of concrete mix made with and without coal bottom ash of cubes size 1.5 cm × 1.5 cm × 1.5 cm and the results were determined at 7, 28, 56, and 112 days. It was observed that for 10 % and 20 % sand replacement the compressive strength was increased by 4.6 %, 3.99 %, 0.61%, 0.20 % for 7, 28, 56 and 112 days respectively as compared with controlled concrete.…”
Section: Introductionmentioning
confidence: 99%